Myocardial Scintigraphy in the Evaluation of Cardiac Events in Patients without Typical Symptoms - Smanio,Paola Emanuela Poggio (2015)
Abstract Background: Cardiovascular disease is a leading cause of death in the world and in Brazil. Myocardial scintigraphy is an important noninvasive method for detecting ischemia in symptomatic patients, but its use in asymptomatic ones or those with atypical symptoms is yet to be defined. Objective: To verify the presence of major cardiac events in asymptomatic patients or those with atypical symptoms (atypical chest pain or dyspnea) that underwent myocardial scintigraphy (MS), over a period of 8 years. Secondary objectives were to identify cardiac risk factors associated with myocardial scintigraphy abnormalities and possible predictors for major cardiac events in this group. Methods: This was a retrospective, observational study using the medical records of 892 patients that underwent myocardial scintigraphy between 2005 and 2011 and who were followed until 2013 for assessment of major cardiac events and risk factors associated with myocardial scintigraphy abnormalities. Statistical analysis was performed by Fisher’s exact test, logistic regression and Kaplan-Meyer survival curves, with statistical significance being set at p ≤ 0.05. Results: Of the total sample, 52.1% were men, 86.9% were hypertensive, 72.4% had hyperlipidemia, 33.6% were diabetic, and 12.2% were smokers; 44.5% had known coronary artery disease; and 70% had high Framingham score, 21.8% had moderate and 8% had low risk. Of the myocardial scintigraphies, 58.6% were normal, 26.1% suggestive of fibrosis and 15.3% suggestive of ischemia. At evolution, 13 patients (1.5%) had non-fatal myocardial infarction and six individuals (0.7%) died. The group with normal myocardial scintigraphy showed longer period of time free of major cardiac events, non-fatal myocardial infarction (p = 0.036) and death. Fibrosis in the myocardial scintigraphy determined a 2.4-fold increased risk of non-fatal myocardial infarction and five-fold higher risk of death (odds ratio: 2.4 and 5.7, respectively; p = 0.043). Conclusion: The occurrence of major cardiac events in 8 years was small. Patients with fibrosis at MS had more major events, whereas patients with normal MS result had fewer major cardiac events, with higher survival.